Wage Inequality and Economic Crime in Decision No. 1393 K/Pid/2023 - Dinata, Hendra Marta, M. Ruhly Kesuma (IJBLE Scientific Publications Community Inc., 2025)
This article discusses the relationship between wage inequality and economic crime in the context of the Supreme Court's decision Number 1393 K/Pid/2023. This study examines the legal arguments for rejecting the reason for cassation based on the economic condition of the defendant, specifically wages below the minimum standard, in the case of theft of company assets by two employees. The analysis focuses on the normative limitations of Article 253 of the Criminal Code and the lack of consideration for socio-economic factors in criminal practice in Indonesia. With a normative legal approach and structural criminology, this article critiques a formalistic criminal law approach that prioritizes form over substance. It was concluded that Indonesia's criminal justice system has not been fully responsive to the socio-economic motives of perpetrators, and it is necessary to adopt a more humane criminal paradigm through progressive, restorative, and integrative considerations between criminal law and labor norms.